Physical and Chemical Features of Hydrogen Combustion and Their Influence on the Characteristics of Gas Turbine Combustion Chambers; Applied Sciences; Vol. 13, iss. 6 - Shchepakina E. A. Elena Anatolievna; Zubrilin I. A. Ivan Alexandrovich; Kuznetsov A. Yu. Alexey Yurievich; Tsapenkov K. D. Konstantin Dmitrievich; Antonov D. V. Dmitry Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Yakushkin D. V. Denis Vladimirovich; Ulitichev A. G. Alexander Gennadievich; Dolinskiy V. A. Vladimir Alexandrovich; Morales M. H. Mario Hernandez (2023, 2023)
Title screen